Risk Factors Associated with Limb Amputation in Necrotizing Fasciitis at dr. Cipto Mangunkusumo General Hospital Jakarta - Pratama, Dedy; Harisandi, Sandra (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Early diagnosis and management of necrotizing fasciitis of the extremities has an impact on mortality and morbidity. Studies have shown a correlation of risk factors (e.g. gender, gangrene, and comorbid) with increased risk of amputations in necrotizing fasciitis. Method. A cross sectional study conducted on subjects diagnosed as necrotizing fasciitis managed at dr.Cipto Mangunkusumo General Hospital during January 2012 to December 2015. The subject characteristics i.e. gender, age, comorbid, wound presentation, pulse, respiratory rate, temperature, serum creatinine level, hemoglobin content, sodium, and leukocytes level were the variables subjected to statistical analysis. Results. There were 70 subjects enrolled; fifty percent were males. and 60% were less than 60 years old. The most comorbid found were hypertension (34.3%), diabetes mellitus (28.6%). and kidney disease (22.9%). Amputation occurred in 24.28% subjects. Female was shown to have a greater risk of amputation than male (p = 0.012). Diabetes mellitus, skin necrosis, gangrene and serum creatinine level ≥1.6 mg/dL were significantly associated as an amputation risk factor (p <0.005). Based on modified LRINEC scoring, 45 subjects were of high risk and 25 were of medium risk. Multivariate analysis showed three strong predictors for amputation were diabetes mellitus (risk ratio 7.685; 95% CI 1.898– 31.122; p = 0.004), gangrene (risk ratio 6.151; 95% CI 1.539–24.584; p = 0.010), and serum creatinine level >1.6 mg/dL (risk ratio 4.098; 95% CI; 0.937–17.255; p = 0.054). Conclusion. Diabetes mellitus, gangrene, and serum creatinine level >1.6 mg/dL referred as risk factors associated with limb amputation in necrotizing fasciitis .